2019
DOI: 10.1620/tjem.248.297
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Low Albumin Levels Are Associated with Severe Community-Acquired Pneumonia in Pregnancy: A Case-Control Study

Abstract: Community-acquired pneumonia (CAP) is the most common form of pneumonia in pregnancy and may lead to severe adverse maternal and fetal outcomes. Severe CAP (SCAP) is defined as the need for invasive mechanical ventilation and with septic shock with the need for vasopressors. This study aimed to analyze the clinical characteristics and factors associated with SCAP in pregnancy. The present study was a case-control study of pregnant women hospitalized between September 2012 and September 2017 at nine tertiary ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…In some studies of pregnancy with community-acquired pneumonia, anemia, hypoproteinemia, and low BMI were proved as risk factors for severe community-acquired pneumonia. 23 Among the patients with COVID-19, we also found that level of hemoglobin and albumin was significantly lower in severe cases than that of mild cases, 24…”
Section: Con S Ider Ati On S On the Delivery Manag Ement For S E Vementioning
confidence: 78%
“…In some studies of pregnancy with community-acquired pneumonia, anemia, hypoproteinemia, and low BMI were proved as risk factors for severe community-acquired pneumonia. 23 Among the patients with COVID-19, we also found that level of hemoglobin and albumin was significantly lower in severe cases than that of mild cases, 24…”
Section: Con S Ider Ati On S On the Delivery Manag Ement For S E Vementioning
confidence: 78%
“…The results found that there were positive correlations between serum resistin and inflammatory cytokines among CAP patients. Furthermore, an earlier project from our research group found that blood routine indices, liver function, and renal function can serve as indicators for pneumonia (27)(28)(29).…”
Section: Discussionmentioning
confidence: 89%
“…Although no study has reported that HB values can predict the occurrence of CIP, He et al. found that low HB was independently associated with the occurrence of community-acquired pneumonia in pregnant women ( 27 ). HB plays the role of transporting oxygen, and its deficiency is related to hypoxia, which may promote the deficiency of lung function, making patients susceptible to pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that a low serum ALB level with pembrolizumab was an independent predictor of CIP (25), consistent with the finding of our study. In addition, Hu et al found that increased ALB concentration was associated with improved lung function (26). ALB is an acute phase reactant that can show the inflammatory state of the body; a decrease in ALB may be related to the inflammatory state of the body, and these mechanisms lead to the occurrence of CIP.…”
Section: Characteristics Numbermentioning
confidence: 99%